TINJAUAN YURIDIS MENGENAI RUANG TERBUKA HIJAU DI KOTA SAMARINDA BERDASARKAN UNDANG-UNDANG NOMOR 26 TAHUN 2007 TENTANG PENATAAN RUANG - Tri Wahyudi (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT The purpose of this study was to know about the Green Open Space Provision pursuant to Article 29 of Act No. 26 of 2007 on the arrangement of space in the city of Samarinda undertaken by the municipality and the constraints faced by the city government, as well as the solution. Based on the results of the study authors concluded that the provision of green open space provision under Section 29 of Act No. 26 of 2007 on the arrangement of space in Samarinda undertaken by the Government of Samarinda is the preparation of the Regional Spatial Regulation of Samarinda as a substitute for local regulation implementation guide RUTRK City Samarinda which is not relevant at this time with the development of National Development. As a form of coordination of spatial planning in order to obtain a minimal proportion of the value of green space by 30 percent of the total area of the city in the form of planning, utilization and control of urban space. This can be achieved with good cooperation from the City Government, Public, Private parties, and with non-governmental organizations.